A Percolation Model for Piezoresistivity in Conductor–Polymer Composites. Issue 2 (3rd December 2018) - Wang, Mingyi; Gurunathan, Ramya; Imasato, Kazuki; Geisendorfer, Nicholas R.; Jakus, Adam E.; Peng, Jun; Shah, Ramille N.; Grayson, Matthew; Snyder, G. Jeffrey
Abstract: Insulating polymer composites with conductive filler particles are attractive for sensor applications due to their large piezoresistive response. Composite samples composed of a polymer matrix filled with particles of doped semiconductor that gives a piezoresistive response that is 10 5 times larger than that of bulk semiconductor sensors are prepared here. The piezoresistance of such composite materials is typically described by using a tunneling mechanism. However, it is found that a percolation description not only fits prior data better but provides a much simpler physical mechanism for the more flexible and soft polymer composite prepared and tested in this study. A simple model for the resistance as a function of applied pressure is derived using percolation theory with a conductivity exponent, s . The model is shown to fit experimental piezoresistive trends with the resistance measured both perpendicular and parallel to the pressure direction. Abstract : The pressure‐dependent resistance observed in polymer–conductor composites is modeled according to percolation theory under volume deformation. This new piezoresistive model predicts both a threshold for resistance under pressure and a power‐law resistance versus pressure beyond that threshold.